Heterocyclic Monoazo Dyes Derived from 2-Amino Benzoxazole and Their Application of polyester Fibre - Desai, T.R.; Desai, K.R. (Asian Journal of Chemistry, 2010)
Nine azo disperse dyes of the type 2-arylazo benzoxazole have been synthesized by using 2-hydroxy phenylthiourea, lead oxide, then after diazotisation and coupling with various substituted amino benzene derivatives. Dyeing properties of these dyes on polyester fibre were assessed. These dyes were characterised by elemental analysis and IR spectra.